Estudio de la seguridad alimentaria y nutricional de unidades camesinas productoras de café en rediseño agroecológico (Cuenca del río Porce, Antioquia) (2016)
ABSTRACT: Food security is one of the indicators of sustainability of small family farm units. The state of food security has been studied in ten rural households located in Porce river basin in northeastern region of Antioquia department, together with individual nutritional status based on the analysis of Body Mass Index (BMI). After visiting 48 farms in the municipalities of Santo Domingo, Gomez Plata, Santa Rosa, Yolombo and Amalfi, only the farms which met the inclusion criteria to start an agroecological transition were selected in order to become in the future standards of sustainable agriculture for the region. Preliminary assessment of the food security state was considered important to obtain a base line prior to the transition. Ethnographic observation showed that the diet meets a diversified pattern of foods, which mostly are produced in the same farms for self-consumption at home. This means that there is not only food security but there is a degree of sovereignty in food supply. However, the survey of self-rated food security revealed that only half of the households were perceived in normality and instead the other half in mild insecurity. Overweight was found to be the main nutritional problem, involving a greater proportion of women compared to men. The study showed agro-ecosystem features could threaten in the medium term current food security conditions, and therefore some criteria are discussed for farm protection against eventualities with food insecurity.